MASA KEEMASAN MENGHAFAL : URGENSI DALAM PENGUASAAN BAHASA ASING PADA SISWA TINGKAT MENENGAH (KAJIAN PSIKO, SOSIO, DAN LINGUISTIK): indonesia - Nafi’ul Huda; Muqimah Liwais Sunnah; Fikri Haji Yakub, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Adolescence is a period of cognitive development that shows an increase in memory capacity and information processing ability, making it the right phase to optimize memorization activities. This condition is relevant to the learning of foreign languages, especially Arabic, which requires mastery of mufrodat as the basis for language competence. This study aims to explain the urgency of utilizing adolescent golden age in mastering foreign languages in secondary school students through psychological, sociological and linguistic perspectives. The method used is a literature study by examining the theory of cognitive development, learning characteristics, and social factors that affect language acquisition, such as the learning environment, peer interaction, motivation, and teacher teaching patterns. The results of the study show that the ability to memorize in adolescence contributes significantly to the improvement of vocabulary mastery, and its effectiveness is influenced by the social conditions surrounding the learning process. The implications of this study emphasize the need for a learning strategy that integrates adolescents' cognitive potential with the support of the social environment so that Arabic language mastery in secondary students can develop more optimally.